2017
DOI: 10.1039/c6cc09203a
|View full text |Cite
|
Sign up to set email alerts
|

Metal-induced supramolecular chirality inversion of small self-assembled molecules in solution

Abstract: A non-covalent self-assembled chiral alanyl aminopyridine ligand exhibits supramolecular chirality in solution, independent of the organic solvent used. The supramolecular chirality of the assemblies is completely inverted by complexation to zinc ions. To date, such a supramolecular metal-ligand system has not been reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…The proximity of cyclohexane rings is evidenced by the distance of 4.672 Å between farthest carbon atoms what is comparable to the distance found in the crystal structure of a 1,3,5‐cyclohexanetriamide,[9e] where the stacked cyclohexane rings also exhibit M ‐helical chirality.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The proximity of cyclohexane rings is evidenced by the distance of 4.672 Å between farthest carbon atoms what is comparable to the distance found in the crystal structure of a 1,3,5‐cyclohexanetriamide,[9e] where the stacked cyclohexane rings also exhibit M ‐helical chirality.…”
Section: Resultssupporting
confidence: 70%
“…J ( 195 Pt, 31 P) ≈ 3650 Hz were assigned as cis ‐ square planar isomer. [9c] The singlet line for the trans ‐isomer was found at about δ ≈ 20.5 ppm, the satellite doublet originating from the J ( 195 Pt, 31 P) coupling was too weak to be obtained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the coordination of metal ions with chiral molecules was also applied as as trategy to adjust supramolecular chirality. [28] Kirin et al [29] reported that ah ydrogen-bonded chiral aminopyridine ligand exhibited supramolecular chirality in solution, independent of the organic solvent used. However, the supramolecular chirality was completely inverted by complexation to zinc ions.…”
Section: Dynamic Modulation At the Intramolecular Levelmentioning
confidence: 99%
“…Mode transformation of acylaminopyridine molecules by additive zinc ions, resulting in the reversal of supramolecular chirality.R eproduced with permission from Ref [29][40]…”
mentioning
confidence: 99%